2015
DOI: 10.1111/apt.13331
|View full text |Cite
|
Sign up to set email alerts
|

Randomised clinical trial: a dose‐ranging study of vonoprazan, a novel potassium‐competitive acid blocker, vs. lansoprazole for the treatment of erosive oesophagitis

Abstract: SummaryBackgroundThe potassium‐competitive acid blocker vonoprazan (VPZ) has potent acid‐inhibitory effects and may offer clinical advantages over conventional therapy for acid‐related disorders.AimTo investigate the efficacy and safety of VPZ in patients with erosive oesophagitis (EO).MethodsIn this multicentre, randomised, double‐blind, parallel‐group, dose‐ranging study, patients ≥20 years with endoscopically confirmed EO [Los Angeles (LA) grades A−D] received VPZ 5, 10, 20 or 40 mg, or lansoprazole (LPZ) 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
192
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(202 citation statements)
references
References 32 publications
10
192
0
Order By: Relevance
“…A dose of 40 mg was selected as the therapeutic dose for this study because in a previous phase II study,10 40 mg was the maximum dose used and doses ≥20 mg were expected to be used for different indications. The supratherapeutic dose in this study was 120 mg because it was the highest dose administered in healthy subjects in a phase I study4 and was well tolerated.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A dose of 40 mg was selected as the therapeutic dose for this study because in a previous phase II study,10 40 mg was the maximum dose used and doses ≥20 mg were expected to be used for different indications. The supratherapeutic dose in this study was 120 mg because it was the highest dose administered in healthy subjects in a phase I study4 and was well tolerated.…”
Section: Methodsmentioning
confidence: 99%
“…Electrocardiogram (ECG) parameters for vonoprazan in clinical trials have not shown any clinically meaningful QT/QTc prolongation 4, 5, 9, 10, 11, 12, 13, 14. Despite the lack of cardiac arrhythmic events in the extensive clinical development program, a thorough QT study was conducted to provide a definitive assessment of the effects of vonoprazan on the QT interval.…”
mentioning
confidence: 99%
“…Characteristics of vonoprazan are the rapid onset, high potency, and long duration of its acid secretion-inhibitory effect 25,26 . Excellent results have also been reported by its clinical trials against reflux esophagitis 28,29 . However, there is also concern over adverse effects associated with its strong acid-suppressive effect.…”
Section: -4) Switching To Vonoprazanmentioning
confidence: 80%
“…In addition, the intragastric pH following VPZ treatment (pH 5.2) has been identified to be significantly higher than that following esomeprazole treatment (pH 3.0) on day 1 of therapy (18). The superior efficacy of VPZ compared with PPIs has been reported in various gastrointestinal diseases (19)(20)(21)(22).…”
Section: Eradication Rate % (N) -------------------------------------mentioning
confidence: 99%